Does Women’s Reproductive Health and Empowerment Affect Female Labor Participation in ASEAN? - Al Faizah, Salma Audiena; Mafruhah, Izza; Sarungu, Julianus Johnny (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2020)
This research aims to analyze the effect of women’s reproductive health and women’s empowerment on female labor force participation (FLFP) in ASEAN countries. This type of research is quantitative research with panel data types from 9 (nine) ASEAN countries during the period 2010-2017. The resultsshow that countries with high levels of women’s reproductive health and women’s empowerment also have high levels of female labor participation.